2012
DOI: 10.4049/jimmunol.1102667
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Inhibitor 6 Is Required To Protect Dendritic Cells from the Kiss of Death

Abstract: How dendritic cells (DC) present antigen to cytotoxic T cells (CTL) without themselves being killed through contact mediated cytotoxicity (so called kiss of death) has proven to be controversial. Using mice deficient in Serine Protease Inhibitor 6 (Spi6) we show that Spi6 protects DC from the kiss of death by inhibiting granzyme B (GrB) delivered by CTL. Infection of Spi6 KO mice with Lymphocytic Choriomeningits virus (LCMV) revealed impaired survival of CD8α DC. The impaired survival of Spi6 KO CD8α DC result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…[39][40][41] We and others have shown that only a small fraction (,1%) of locally inoculated DCs can migrate to the draining lymph nodes, whereas most remain at the site of immunization. 13,42,43 IV-delivered DCs are also insufficient to traffic to the spleen and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] We and others have shown that only a small fraction (,1%) of locally inoculated DCs can migrate to the draining lymph nodes, whereas most remain at the site of immunization. 13,42,43 IV-delivered DCs are also insufficient to traffic to the spleen and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The H-2D b -restricted peptide of LCMV-GP (GP [33][34][35][36][37][38][39][40][41] ; KAVYNFATM) was purchased from the Dalton Chemical Laboratory (Toronto, Canada). Peptides were dissolved in distilled water and stored at 220°C.…”
Section: Peptidesmentioning
confidence: 99%
“…*p , 0.05, **p , 0.01, ***p . 0.001. or that these cells may have received survival signals through interactions with Ag-specific T cells (45,46). Regardless, the crucial role of langerin + CD8a + DCs in cross-priming is not simply because they are the only cells capable of cross-presentation, because Ag was effectively processed and presented in their absence (Fig.…”
Section: Cd8amentioning
confidence: 99%
“…1: premetastatic Results from one experiment in the study appears to be in favor of the idea that myeloid cells presenting activated STAT3 have some level of intrinsic resistance to CTL killing, as BM-derived macrophages stimulated by TCM and pulsed with the OVA peptide in vitro were less efficiently killed when they were STAT3-positive rather than when STAT3-deficient [15]. Interestingly, BMderived DCs have been previously reported to acquire resistance to granzyme B-dependent killing by CD8 + T cells, through the induction of the serpin serine protease inhibitor 6 (SPI-6) [18,19]. In that case, the acquired resistance of DC is thought to favor a sustained activation and expansion of immune effector cells.…”
mentioning
confidence: 99%
“…Interestingly, BMderived DCs have been previously reported to acquire resistance to granzyme B-dependent killing by CD8 + T cells, through the induction of the serpin serine protease inhibitor 6 (SPI-6) [18,19]. In that case, the acquired resistance of DC is thought to favor a sustained activation and expansion of immune effector cells.…”
mentioning
confidence: 99%